Postdischarge Iron Status in Very Preterm Infants Receiving Prophylactic Iron Supplementation after Birth - Landry, Carmen; Dorling, Jon; Kulkarni, Ketan; Campbell-Yeo, Marsha; Morrison, Lisa; Ledwidge, Joyce; Vincer, Michael; Ghotra, Satvinder (The Journal of pediatrics, 2022)
To determine postdischarge iron status and associated factors in very preterm infants. A retrospective cohort study was conducted through a provincial database on all very preterm infants born in Nova Scotia between 2005 and 2018. As a standard of care, all infants received prophylactic iron supplements starting at 2-4 weeks of chronological age and were tested for iron deficiency at 4 or 6 months corrected age. Iron deficiency was defined as serum ferritin <20 g/L at 4 months or <12 g/L at 6 months. Multivariate logistic regression analysis identified factors associated with iron deficiency. Among 411 infants, 132 (32.1%) had iron deficiency and 11 (2.7%) had iron deficiency anemia. The prevalence of iron deficiency decreased over time, from 37.6% in 2005-2011 to 25.8% in 2012-2018. Gestational hypertension in the mother (P = .01) and gestational age <27 weeks (P = .02) were independent risk factors for iron deficiency. In addition, the odds of iron deficiency were lower in the mixed-fed group (ie, with breast milk and formula combined) compared with the exclusive formula-fed group (P = .01). Iron deficiency was prevalent in 32% of the very preterm infants despite early iron prophylaxis. These results demonstrate the importance of monitoring iron stores during preterm follow-up. Information about risk factors is important to mitigate iron deficiency in very preterm infants.